Kesetaraan dalam Perbedaan Gender di Lingkungan Gereja Masehi Injili Halmahera: Sebuah Perspektif Feminisme - Pakka, Jeane Prescilia (JURNAL TERUNA BHAKTI, 2022)
This study aims to explain the causes of differences in position and position between women and men that occur in the Evangelical Christian Church in Halmahera (hereinafter referred to as GMIH) especially in one congregation and how the church responds to this. The research method in writing this article is a qualitative descriptive research method with steps such as; observation, interview, and literature study. The position and role of women both in the family, community and in the church, is actually not something new anymore, because people have been struggling with it for a long time, especially women themselves. The difference in position between women and men in the church is due to the strong influence of theological teachings in the Bible, patriarchal culture and local culture which are a source of inspiration and motivation for believers and the influence of the culture adopted by the local congregation. As the Body of Christ, the church is reminded to carry out its three (3) duties in this world well, namely; witness, fellowship and serve. The church must be a "home for all people" which means the church must be open to anyone, young, old, women and men regardless of ethnicity, race and culture because all are one in Christ Jesus